The Positive Impact of Perceived Union Support on Union Member Work Meaningfulness: Examining Mechanisms and Boundary Conditions. (December 2019) - Cardador, M. Teresa; Grant, Brandon C.; Bruno, Robert
Meaningful work has been linked to consequential individual and organizational outcomes, and has, therefore, become an important topic of study. Yet there is a paucity of research examining the effect of unions on members' work meaningfulness. In a field sample, using a time-lagged survey methodology, we examined the effect of perceived union support on members' perceptions of work meaningfulness, and tested perceived union fulfillment of workers' psychological needs as a mediator. Additionally, we examined the conditional effect of union identification on these relationships. We find that supportive unions foster work meaningfulness via psychological need fulfillment, but these relationships are not conditioned on union identification.